The effect of channa striatus as an adjuvant therapy in treatment of allergic rhinitis - Dhevi Susibalan, Bathma (2015)
Introduction: Allergic rhinitis is a Type 1 mediated hypersensitivity reaction which is characterized by one or more of the following symptoms which is sneezing, rhinorrhea, nasal congestion and nasal itchiness. Management of allergic rhinitis includes patient education and counseling, pharmacotherapy, and allergen-specific immunotherapy. In this study, we were determining the role of channa straitus as a adjuvant therapy in treatment of allergic rhinitis Objectives: To detemine the therapeutic efect of channa striatus and to compare the total nasal symptom score and levels of IgE between channa straitus and placebo group. Methodology: There were 70 patients aged 18 to 50 years old, diagnosed allergic rhinitis based on total symptoms score, nasoendoscopy findings, and positive skin prick test were involved in this prospective, randomized, double blinded, comparative clinical trial. They were divided equally into 2 groups which is channa and placebo group. The patients were screened with detailed history, physical examination and nasoendosopy.Baseline FBC, BUSE, LFT, and IgE levels were obtained prior to commencement of treatment. Both groups were treated with the same conventional treatment, antihistamine (levocetrizine 5mg) with local corticosteroid nasal spray (Avamys nasal spray). Assessment of compliance, drug diary, adverse effects, symptoms score and nasendoscopy were made at Week 0, 2th, and 6th.. Serum IgE levels were measured at week 0 and 6th. Results: Channa group showed significant improvement in nasal symptoms such as nasal blockage (p=0.034) and nasal itchiness (p=0.022), non-nasal symptoms such as eye itchiness (p=0.032) and symptoms in general (p=0.026). IgE levels were significantly lower in Channa group compared to placebo (p-value <0.001).There were no statistical significant in term of nasal discharge, sneezing, palate itchiness, and smell score. There were no serious adverse reactions reported in the channa group. Conclusions: Channa striatus has a beneficial role in improving nasal and non-nasal symptoms with reduction in IgE levels in patients suffering from allergic rhinitis.